KONSEP PENDIDIKAN IKHWAN AL-SHAFA DAN RELEVANSINYA DENGAN DUNIA POSTMODERN - Rahman Afandi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2019)
Abstract: The Ikhwan al-Shafa is an organization established by a group of people (mujtahidin) consisting of philosophers, who focused their attention on the field of da'wah and education, that developed at the end of the second century Hijrah in the city of Basra, Iraq. It is a discussion and teaching forum. In general, its emergence is motivated by concerns about the implementation of Islamic teachings that have been contaminated by teachings from outside Islam at that time, and to revive love for science among Muslims. They compiled 51 agreements known as the "Rasail Ikhwan al-Shafa" (Ikhwan al-Shafa agreement). The background of Rasail Ikhwan al-Shafa writing came from dissatisfaction with the implementation of the Islamic education and lifestyle at that time. This organization viewed education with a rational and empirical view, or a combination of intellectual and factual views. They viewed science as a description of something that could be known in nature, the knowledge produced by human thought occurs because it receives information materials sent by the five senses. Some of the Ikhwan al-Shafa's concepts or thoughts about education have an urgent relevance to education that is applied in the current postmodern era. Whether it's how to get knowledge, teacher competency standards, goals, curriculum and methods that are used. Keywords: Concept, Education, Ikhwanas-Shafa, Relevance, Postmodern.